Clinging to the past: Circulation policies in academic libraries in the United States. Issue 2 (3rd April 2018) - Wilson, Duane; Roberts, Brian
Abstract: This study reports on a national survey of circulation policies in academic libraries in the United States. Circulation policies are similar at most responding libraries and are typically restrictive, though some differences exist based on library type. Associates granting institutions tend to have less generous circulation periods, and PhD granting institutions tend to have more generous renewal policies. Despite dramatic changes in print use, libraries have typically not adjusted their circulation policies to reflect the current environment. Libraries should evaluate their circulation policies and seek for ways to provide more generous policies to better serve the needs of their patrons.